SPSS for intermediate statistics use and interpretation - Leech, Nancy L.; Barrett, Karen Caplovitz; organ, George A. (George Arthur) (Lawrence Erlbaum Associates, 2008)
Helps students learn to analyze and interpret research data using SPSS by demonstrating how to compute a variety of statistics covered in intermediate statistics courses. This book introduces several related statistics and provides instructions on how to run them and interpret the outputs